2015
DOI: 10.1111/pme.12721
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine 5% Patch for Treatment of Acute Pain After Robotic Cardiac Surgery and Prevention of Persistent Incisional Pain: A Randomized, Placebo-Controlled, Double-Blind Trial

Abstract: Lidocaine 5% patches did not reduce acute or persistent pain in patients having robotic thoracic surgery, though pain scores were low in both treatment groups. Clinicians should choose alternative analgesic approaches in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 29 publications
(51 reference statements)
0
27
0
Order By: Relevance
“…They also used several continuous pain scales (verbal rating scale (VRS), visual analogue scale (VAS), numeric rating scale (NRS), bodily pain sub-component of the Short Form Health Survey (SF-36)). Nine studies did not record pain as a dichotomous outcome but only used continuous pain scales (Blumenthal 2005; Chiu 2008; Gupta 2006; McKeen 2014; O’Neill 2014; Singh 2013; Sprung 2006; Vrooman 2015; Wodlin 2011). One did record pain as a dichotomous out-come but did not report it in the manuscript, and provided the review authors with the data via email (Kurmann 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also used several continuous pain scales (verbal rating scale (VRS), visual analogue scale (VAS), numeric rating scale (NRS), bodily pain sub-component of the Short Form Health Survey (SF-36)). Nine studies did not record pain as a dichotomous outcome but only used continuous pain scales (Blumenthal 2005; Chiu 2008; Gupta 2006; McKeen 2014; O’Neill 2014; Singh 2013; Sprung 2006; Vrooman 2015; Wodlin 2011). One did record pain as a dichotomous out-come but did not report it in the manuscript, and provided the review authors with the data via email (Kurmann 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Null bias might cause studies to underestimate the benefit of regional anaesthesia for the prevention of persistent pain after surgery, if the regional anaesthesia interventions were not effectively delivered (Higgins 2011a; Woods 1995). Indeed, a number of included studies reported no improved pain control in the immediate postoperative period in the experimental (regional anaesthesia) group, as evidenced by inconsequential differences in pain scores between groups perioperatively, or similar requirements of rescue analgesic medications between groups in the immediate postoperative period (Barkhuysen 2010; Baudry 2008; Bollag 2012; Can 2013; Choi 2016; Fassoulaki 2000; Ibarra 2011; Ju 2008; Karmakar 2014; Katz 1996; Lam 2015; Lee 2013; Liu 2015; Loane 2012; McKeen 2014; Micha 2012; Purwar 2015; Singh 2013; Smaldone 2010; Terkawi 2015b; Vrooman 2015; Xu 2017; Zhou 2016). Two review authors therefore extracted information on null bias for each included study and documented their judgement with supporting evidence (see: Characteristics of included studies).…”
Section: Methodsmentioning
confidence: 99%
“…[100][101][102] Thoracic Epidural Anesthesia Thoracic epidural anesthesia is associated with a lower incidence of cardiopulmonary complications and provides excellent postoperative pain control 75,[103][104][105] Despite studies showing decreased pain scores and opioid consumption in the acute postoperative period, no reduction in chronic pain incidence or severity has been shown. 106,107 Intrathecal Opioids Intrathecal opioids are often used in fast-track cardiac anesthesia to improve acute postoperative pain scores.…”
Section: Transdermal Lidocainementioning
confidence: 99%
“…Two weeks after surgery, a difference in mean pain score was still apparent (2.00 vs. 2.93), but was no longer statistically significant ( p  = 0.1245) [80]. A randomized, placebo-controlled trial in patients undergoing robotic thoracic surgery concluded that 5% lidocaine plasters did not influence acute or persistent incisional pain, but pain scores in this study were low in both treatment groups [81]. A meta-analysis of efficacy of the plaster in acute pain management reported similar findings, but was limited by the inclusion of only five studies, potential bias from unblinded studies, clinical heterogeneity, and incomplete data regarding adjunct analgesics [82].…”
Section: Supporting Evidence In the Treatment Of Lnpmentioning
confidence: 91%